VALUE IN MALAY COMMUNITIES IN - Desiyani, Eny (The Pontianak State Institute of Islamic Studies, 2018)
Culture comes from the creative process of humans for their good. The change process is a selection process so that it finally produces the best form. This article will reveal the form of Tumbang Apam culture in Malay society in Pontianak. Data was taken through an interview with a number of cultural actors in Pontianak. The researcher concluded that in the Tumbang Apam cultural activities in Malay communities in Pontianak there were educational values. Through this activity every family member and community are taught to help each other, communicate and strengthen friendship relations. This activity is maintained because of the importance of these values for next generation.